(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
The limited availability of forage during the dry season and the suboptimal capacity of farmers in Kota Daro II Village, have contributed to insufficient feed supply for cattle and reduce livestock productivity. The potential of available natural resources offers a viable solution to ensure feed continuity throughout the year. The utilization of swamp grass and agricultural waste through the application of haylage technology can serve as an alternative feed source during the dry season. This activity was a community service program aimed at improving the knowledge and skills of farmers in Kota Daro II Village in utilizing swamp grass haylage supplemented with cassava leaves as an alternative feed source during times of feed shortages. This activity was carried out at the Kota Daro II Village Hall on October 8, 2025, with education and training methods for farmers through counseling on the introduction of haylage technology and training, demonstration of haylage production, which was attended by 25 farmers. Evaluation of haylage results after 21 days of storage to see physical quality and palatability testing of haylage. The results showed that the knowledge, understanding, and skills of farmers in Kota Daro II Village had improved regarding the application of haylage technology in utilizing swamp grass and agricultural waste as alternative feed during the dry season. The training was increased farmers’ understanding by 40–46% regarding haylage technology using swamp grass and agricultural waste. Additionally, the interest and motivation of farmers on how to make haylage was quite good, which was marked by a 100% attendance percentage and 60% farmers in interactive discussions.